Traditional Sanctions Against the Button Tribe Elopement in the Labuhan Regional Court Judge - Mg. Endang Sumiarni; Sekhar Chandra (Faculty of Law, Musamus University, 2023)
This research aims to explore the application of customary sanctions in eloping cases that are resolved through lawsuits in court through the existence of Decision No. 4 / Pdt.G / 2020 / PN Lbh. The elopement was carried out by a male woman who is a buton tribe outside the buton area. The family of the woman as plaintiff filed a lawsuit for material and immaterial damages, but the lawsuit was declared indible by the Panel of Judges. In this study conducted an in-depth review of whether the plaintiff's lawsuit can be interpreted based on customary law, whether legal considerations and judge's rulings have been oriented to Buton customary law. Research uses normative research methods, with secondary data in the form of primary legal materials and secondary legal materials, as well as court rulings. Analysis of primary legal materials is carried out description, systematization, analysis, interpretation and assessing buton customary law. Legal considerations used by judges include relative competence which in essence the Labuha District Court is not authorized to examine and adjudicate cases a quo because previously customary deliberations have been carried out 3 (three) times in resolving aquo cases, which then imposed customary fines based on buton tribal customs. by indigenous buton tribal figures to Defendant, the reason Plaintiff is not a buton tribe but a kei tribe, therefore does not have the right to file a lawsuit for customary fines buton against Defendant so that the Plaintiff's lawsuit is wrong target, and Defendant is incomplete, there are still people who must act as Defendants or withdrawn Defendants and therefore the lawsuit contains error in persona in the form of plurium litis consortium , in the sense that the lawsuit filed is less.